Kompetensi Pedagogik Guru Dalam Menggunakan Media Pembelajaran Di Madrasah Ibtidaiyah, Studi Kasus Di MIN Jejeran - Wahyu Diantoro Hidayat (Universitas Cokroaminoto Yogyakarta, 2018)
Learning media is very important to be used by teachers to make it easier for students to understand what is conveyed by the teacher and its learning goals expected. The media used by teachers at State Islamic Primary School (MIN) Jejeran are LCD (Liquid Crystal Display), projector screens, subject books, Student Worksheets (Student Worksheets), Power points, Main Manager, Ms. Word and the environment that is set-up in such a way that can be used as a medium in learning.